Translation Strategies of Lontar Yusup Banyuwangi in Bernard Arps’ Tembang in Two Traditions: Performances and Interpretation of Javanese Literature - Selvy Kurniasari; Dewi Masitoh; Naufal Anfal; Wiwin Indiarti (Ethical Lingua: Journal of Language Teaching and Literature, 2019)
The article is based on research done with the descriptive-qualitative approach and is an embedded-case study meant the result could not be generalized. The primary data are Javanese cultural terms of Lontar YusupBanyuwangi and the English translation found in the book of Bernard Arps (a Dutch anthropologist) entitled Tembang in Two Traditions: Performances and Interpretation of Javanese Literature. LontarYusup is the only manuscript in Banyuwangi still read routinely in rituals conducted by Osing ethnic group considered as the natives of Banyuwangi. The research aims at unveiling the cultural terms used based on the category and the translation strategies applied. The technique used to collect the data is documentation and the collected data are, then, analyzed by applying content analysis technique. The research results that there are 141 cultural terms classified in 10 cultural categories: food (4), cultural materials (23), arts (2), buildings (5), socio-culture (48), religion (36), gesture (10), ecology (7), habit (7), and clothing (3). Those Javanese cultural terms are then translated into English by utilizing 8 translation strategies: synonym (62.07%), pure borrowing (16.55%), transposition (0.69%), structural addition (4.83%), descriptive equivalent (11.03%), subtraction (0.69%), componential analysis (1.38%), and cultural equivalent.